The Stepmother in Ancient Egypt: A Literary and Sociological Approach - Díaz Rivas, Helena (Revista del Instituto de Historia Antigua Oriental ’Dr. Abraham Rosenvasser’, 2024)
The archetype of the stepmother is a universal cultural construct. Her wickedness has reached us through several tales that describe her as a ruthless, manipulative, and capricious woman, capable of doing anything on her own benefit and in favor of her offspring. The stepmother also plays a role in Ancient Egypt. The pejorative view of her is rooted in the threat she posed. Her arrival and the auspices of new offspring could be seen by the children of the first marriage as dangerous, and could involve a “struggle of interests” over the question of inheritance. There was a dichotomy in which the normative social discourse, according to which the natural condition of Egyptian adults was to be married (and have children), clashed with the private interests of certain members of the family unit in the case of remarriages.